Kontribusi Alokasi Dana Desa Pada Peningkatan Ekonomi Masyarakat (Studi Kasus Desa Teluk Langkap, Kabupaten Tebo) - Subhan Subhan (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2019)
The purpose of this study is to describe and analyze the plannning, implementing, evaluating and controlling of village fund allocation. The method used is descriptive qualitative through observation, interviews, and documentation on the primary data, namely village officials in Teluk Langkap village. Based on the results of the analysis, the sorting and grouping of data shows that the main obstacle is the lack of quality of human resources in terms of knowledge and understanding of laws and the lack of socialization of training and assistance to village officials, guidance is needed in village financial administration so that management is right in the direction. In general, the allocation of village funds can improve the economy of the residents but does not always run smoothly,such as planning for budget allocations that do not go through a joint village forum(musrenbang)